2018
DOI: 10.1017/hpl.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Faraday effect measurements of holmium oxide (Ho2O3) ceramics-based magneto-optical materials

Abstract: Faraday effect measurements of holmium oxide (Ho 2 O 3 ) ceramics-based magneto-optical materials, highly potential material candidates for high-energy laser Faraday isolators, are presented in this paper. Temperature dependence of the Verdet constant of nondoped Ho 2 O 3 ceramics was measured for temperatures 15-305 K at 1.064 µm wavelength. The Verdet constant dispersion for wavelengths 0.5-1 µm and 1.064 µm was measured for both nondoped Ho 2 O 3 ceramics and Ho 2 O 3 ceramics doped with terbium Tb 3+ (0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The results of measuring the Verdet constant for 4% La:Yb 2 O 3 ceramics are shown in Figure 7 in comparison with the widely used TGG material (see Figure 7a) and with some other known magneto-optical materials which are transparent in the spectral range beyond 1.4 µm (see Figure 7b). The dependences of the Verdet constant on the wavelength are obtained by approximating experimental data for a TGG single crystal [32], Dy 2 O 3 ceramics [20] using the approximation formula from [33], Er 2 O 3 ceramics [25], Ho 2 O 3 ceramics [24,35], EuF 2 , NHF single crystals [36], and for some types of magneto-optical glasses: ternary phosphate glass [37] and TeO 2 [38]. and this dependence is very different in the region of absorption bands (0.9-1.1 µm), where it is impossible to use this material as a magneto-optical one.…”
Section: Sintering and Microstructure Of (Yb X La 1−x ) 2 O 3 Ceramicsmentioning
confidence: 99%
“…The results of measuring the Verdet constant for 4% La:Yb 2 O 3 ceramics are shown in Figure 7 in comparison with the widely used TGG material (see Figure 7a) and with some other known magneto-optical materials which are transparent in the spectral range beyond 1.4 µm (see Figure 7b). The dependences of the Verdet constant on the wavelength are obtained by approximating experimental data for a TGG single crystal [32], Dy 2 O 3 ceramics [20] using the approximation formula from [33], Er 2 O 3 ceramics [25], Ho 2 O 3 ceramics [24,35], EuF 2 , NHF single crystals [36], and for some types of magneto-optical glasses: ternary phosphate glass [37] and TeO 2 [38]. and this dependence is very different in the region of absorption bands (0.9-1.1 µm), where it is impossible to use this material as a magneto-optical one.…”
Section: Sintering and Microstructure Of (Yb X La 1−x ) 2 O 3 Ceramicsmentioning
confidence: 99%
“…This review presents the characterization method based upon a modified version of the polarization-stepping technique [44], which has been systematically developed in the recent years [45][46][47][48]. One of the main advantages of this method is that the rotation angle induced in the examined material sample is analyzed based on a large number of angular positions (typically a few hundred) of the analyzing polarization-sensitive element of the experimental detection system.…”
Section: Characterization Of the Verdet Constant As A Function Of Wavmentioning
confidence: 99%
“…This configuration was used in the investigations in Refs. [45][46][47], and its main advantage is the relative simplicity of the setup, compared with the other configurations. Furthermore, assuming we measure the Verdet constant on a single wavelength only (we use a laser probe beam except the broadband source), the spectrometers may be exchanged with a power meter, which even more simplifies the measurement and data analysis.…”
Section: Experimental Setup For the Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, such materials can be other oxides of rare-earth (RE) elements. For example, it has been recently demonstrated that holmium oxide ceramics, in comparison with the TGG, have 1.3 times greater value of the Verdet constant [3, 4]. On the other hand, the rare-earth sesquioxides single crystals are extremely difficult to grow with common techniques, since most of the oxides undergo phase transformations upon heating – cooling process, which could lead to damage of the crystals [5].…”
Section: Introductionmentioning
confidence: 99%